Use of Preventive Services by Men Enrolled in Medicare+Choice Plans - Morales, Leo S. (© American Journal of Public Health 2004, 2004)
Objectives. We examined the effect of demographic and socioeconomic factors on use of preventive services (prostate-specific antigen testing, colorectal cancer screening, and influenza vaccination) among elderly men enrolled in 2 Medicare+Choice health plans. Methods. Data were derived from administrative files and a survey of 1915 male enrollees. We used multivariate logistic regression to assess the effects of enrollee characteristics on preventive service use. Results. Age, marital status, educational attainment, and household wealth were associated with receipt of one or more preventive services. However, the effects of these variables were substantially attenuated relative to earlier studies of Medicare. Conclusions. Some Medicare HMOs have been successful in attenuating racial and socioeconomic disparities in the use of preventive services by older men.